Revisão da literatura de artigos sobre a adoção das normas internacionais de contabilidade e a convergência contábil - Santos, Fernando dos (2014)
This research aims to investigate what has been published about the Adoption of the International Accountancy Norms, its general objective was elaborating a procedure for analysis and selection of Brazilian literature about the theme Adoption of the International Accountancy Norms and Accountancy Convergence. To reach the objective of this work, it was used as a search tool the model Knowledge Development Process-Constructivist (ProKnow-C). To search the articles of the bibliography the data basis Scielo, Speel and Google Scholar were used. At the end of the application of the filtering procedure it was reached a total of 20 articles aligned with the theme of this search. The methodological framework of this search is known as descriptive, on which the characteristics of the articles classified in the bibliography were described, the approach of the problem has been occurred by qualitative method and as research target the documental analysis. The analyzed data were: (i) most relevant Authors, the most highlighted LEMES with three publications, SANTOS, LIMA, LIMA, GRECCO, COVA and CARVALHO with 2 publications each. Other authors had just one publication; (ii) Evolution in Time, the year of 2013 was the period with the greatest amount of publications, contributing with 7 publications, 2010 with 3 publications, 2008, 2009, 2012 with 2 publications and 2006, 2007, 2011 and 2014 with just one; (iii) Place of Publication, with 13 publications through scientific magazines, 6 through congress and only one through journals; (iv) Publications in Journals/ Event, being USP congress the most prolific, publishing 3 articles, ENANPAD Congress, Revista Contabilidade Vista & Revista e Revista Pensar Contábil with 2 publications each. The other organizations participated with only one publication each. In the content it was analyzed: (i) Nature of the objective, 11 articles have a descriptive search character, 3 of descriptive and 2 articles with exploratory character. The other search methods: descriptive and empiric, empiric-analytic and case study appear with just one publication each; (ii) Approach of the Problem, being 10 articles with a quantitative approach of the problem, followed by 7 articles with a qualitative approach and 3 with qualitative/quantitative; (iii) Analysis Method, from the 20 articles chosen for this study, 6 had done content analysis, 5 data analysis, 2 used documental analysis, 1 questionnaire application and 1 case study, and yet, 5 works did not inform the type of analysis used and (iv) Area of Application and Objective of the Studies, the area with the greates application of the studies is directed to the business listed.